Antibacterial Properties of Polysulfone Membranes Blended with Arabic Gum - Souhir Sabri (9553808) (2019)
Polysulfone (PS) membranes blended with different loadings of arabic gum (AG) were synthesized using phase inversion method and the antibacterial properties of the synthesized membranes were tested using a number Gram-negative (Escherichia coli, Klebsiella pneumonia and Pseudomonas aeruginosa) and Gram-positive (Staphylococcus aureus) bacterial species. It was shown that AG addition to the dope polymer solutions essentially changed porous structure, hydrophilicity and zeta potential of the cast PS/AG membranes. These changes were due to the amphiphilic properties of AG macromolecules that contained negatively charged hydrophilic residues. A pronounced decrease in bacterial attachment was seen in the field emission scanning electron microscopy (FESEM) images for PS/AG membrane samples compared to both commercial (Microdyn-Nadir) and bare PS (without AG) membranes. AG loading dependent trend was observed where the prevention of bacterial colonization on the membrane surface was strongest at the highest (7 wt. %) AG loading in the casting solution. Possible mechanisms for the prevention of bacterial colonization were discussed. Significantly, the inhibition of bacterial attachment and growth on PS/AG membranes was observed for both Gram-positive and Gram-negative bacterial models, rendering these novel membranes with strong biofouling resistance attractive for water treatment applications. Other Information Published in: Membranes License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/membranes9020029